Academic women’s negotiation of gender identities in non-elite Chinese universities - Yuan, Boya; Tian, Xiaoming (Frontiers in Psychology, 2023)
This study employs Butler’s concept of identity to unpack how non-elite Chinese university academic women negotiate gender identities under the influence of the wider social discourses around gender in their institutional context. The study includes two empirical investigations of (i) semi-structured interviews and (ii) photovoice interviews with six women academics from six different non-elite Chinese universities. We found that most interviewees tended to value their teacher identity and meanwhile downplay their researcher identity in the professional field; while in the private field, they paid more attention to their mother identity at the cost of downplaying their career development. The study also reveals that, in the process of gender negotiation, the interviewees commonly adopted two strategies: (i) creating space and time for identity performance, and (ii) persuading with selves to accept multiple identities. This article contributes to the understanding of Chinese academic women in non-elite public universities from a Butlerian perspective.